Effects of donor cells' sex on nuclear transfer efficiency and telomere lengths of cloned goats. (25th August 2016) - Liu, H‐j; Peng, H; Hu, C‐c; Li, X‐y; Zhang, J‐l; Zheng, Z; Zhang, W‐c
Contents: The aim of this study was to investigate the effects of donor cells' sex on nuclear transfer efficiency and telomere length of cloned goats from adult skin fibroblast cells. The telomere length of somatic cell cloned goats and their offspring was determined by measuring their mean terminal restriction fragment (TRF) length. The result showed that (i) reconstructed embryos with fibroblast cells from males Boer goats obtained significantly higher kids rate and rate of live kids than those of female embryos and (ii) the telomere lengths of four female cloned goats were shorter compared to their donor cells, but five male cloned goats had the same telomere length with their donor cells, mainly due to great variation existed among them. The offspring from female cloned goats had the same telomere length with their age‐matched counterparts. In conclusion, the donor cells' sex had significant effects on nuclear transfer efficiency and telomere lengths of cloned goats.